Risk factors for inflammatory pseudotumour formation following hip resurfacing. - Glyn-Jones, S; Pandit, H; Kwon, Y; Doll, H; Gill, H; Murray, D (2009)
Metal-on-metal hip resurfacing is commonly performed for osteoarthritis in young active patients. We have observed cystic or solid masses, which we have called inflammatory pseudotumours, arising around these devices. They may cause soft-tissue destruction with severe symptoms and a poor outcome after revision surgery. The aim of this study was to determine the incidence of and risk factors for pseudotumours that are serious enough to require revision surgery. Since 1999, 1419 metal-on-metal hip resurfacings have been implanted by our group in 1224 patients; 1.8% of the patients had a revision for pseudotumour. In this series the Kaplan-Meier cumulative revision rate for pseudotumour increased progressively with time. At eight years, in all patients, it was 4% (95% confidence interval (CI) 2.2 to 5.8). Factors significantly associated with an increase in revision rate were female gender (p < 0.001), age under 40 (p = 0.003), small components (p = 0.003), and dysplasia (p = 0.019), whereas implant type was not (p = 0.156). These factors were inter-related, however, and on fitting a Cox proportional hazard model only gender (p = 0.002) and age (p = 0.024) had a significant independent influence on revision rate; size nearly reached significance (p = 0.08). Subdividing the cohort according to significant factors, we found that the revision rate for pseudotumours in men was 0.5% (95% CI 0 to 1.1) at eight years whereas in women over 40 years old it was 6% (95% CI 2.3 to 10.1) at eight years and in women under 40 years it was 13.1% at six years (95% CI 0 to 27) (p < 0.001). We recommend that resurfacings are undertaken with caution in women, particularly those under 40 years of age but they remain a good option in young men. Further work is required to understand the aetiology of pseudotumours so that this complication can be avoided.